2007
DOI: 10.2146/ajhp060505
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based review of the black-box warning for droperidol

Abstract: Studies show that there is a dose-dependent increase in the rate of adverse cardiovascular events when droperidol is used either alone or in combination with other medications that cause Q-T interval prolongation. At this time, there does not appear to be significant evidence to suggest that serotonin type 3-receptor (5-HT(3)) antagonists are safer than droperidol with regard to Q-T interval prolongation. More studies are needed to determine the safety and efficacy of droperidol when used in doses of 0.625-1.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(50 citation statements)
references
References 28 publications
(40 reference statements)
1
47
0
2
Order By: Relevance
“…Despite the FDA warning, there is no significant evidence that low doses of droperidol used for nausea or vomiting are associated with torsade de pointes. We believe that the FDA black box warning is overly cautious, because the current evidence does not support the need for these monitoring requirements when low doses are used (9). A single low dose of intravenous (i.v.)…”
Section: Droperidolmentioning
confidence: 99%
“…Despite the FDA warning, there is no significant evidence that low doses of droperidol used for nausea or vomiting are associated with torsade de pointes. We believe that the FDA black box warning is overly cautious, because the current evidence does not support the need for these monitoring requirements when low doses are used (9). A single low dose of intravenous (i.v.)…”
Section: Droperidolmentioning
confidence: 99%
“…In particular, FGAs are known to cause both cardiac-related side effects and movement-related side effects such as tardive dyskinesia or dystonia (8,9,(17)(18)(19). Given the black box warning by the U.S. Food and Drug Administration (FDA) issued in 2001, the safety profile of droperidol remains a controversial topic in ED literature, with several studies suggesting its safety in everyday clinical use (19)(20)(21)(22)(23)(24)(25). Although haloperidol has not received a black-box warning from the FDA, the risk of motorrelated side effects is quite common in practice.…”
Section: Introductionmentioning
confidence: 99%
“…A ''black box'' warning was placed on droperidol with regard to the risks of prolonged QTc and torsades de pointes by the Food and Drug Administration (FDA) of the United States. 21 Other studies, however, seemed to report that droperidol was safe in this aspect. [22][23][24] Nuttall and colleagues and Fortney and colleagues reported that IV droperidol up to 1.25 mg was safe in adult surgical patients.…”
Section: Discussionmentioning
confidence: 96%